Qualidade de processamento e envelhecimento fisiológico de tubérculos de batata produzidos durante a primavera e o outono na região central do Rio Grande do Sul - Freitas, Sergio Tonetto de (2006)
Potato tubers can be used as food or seed. Potatoes are mostly sold for tablestock and processing consumptions. Each destination has its own requirements to attend consumers exigencies. The aim of this work was to evaluate the processing quality and physiological aging of potato tubers produced during spring and autumn growing conditions in Rio Grande do Sul (RS). Tubers of 15 potato clones were evaluated for processing quality during spring 2003 and autumn 2004. The best performance of chips color, dry matter, and reduced sugar was obtained with potatoes of the clones SMIJ461-1, SMIJ319-1, SMIJ456-4Y, SMIC148-A, SMIDO40-4RY and SMIH095-1. Among these clones, SMIDO40-4RY and SMIH095-1 were less affected by temperature and sunlight conditions of the RS growing seasons. The clones SMIJ461-1 and SMIJ456-4Y cultivated during spring showed the highest dry matter and the lightest chip color. The physiological aging was studied in potato tubers of the Asterix, SNINIA793101-3 and SMIJ461-1 clones produced during spring and autumn 2004 and stored at 4, 8, 12 and 25°C for 180 days. The physiological aging of the three evaluated clones was affected by the growing conditions. Potato tubers cultivated in autumn and stored at 4 and 8°C remained dormant for 180 days. When tubers were produced during spring, only the clones SMINI793101-3 and SMIJ461-1 stored at 4°C remained dormant for 180 days. The growing conditions and genetic differences influence both processing quality and physiological aging of potato tubers. The storage at low temperature is efficient to delay physiological aging only during the dormant period of the potato tubers.